Assessment Of Predictive Factors Determining Conversion To Open Cholecystectomy In Patients Undergoing Laparoscopic Cholecystectomy (Journal of Pharmaceutical Negative Results, 2022)
Background: Laparoscopic cholecystectomy is the standard of care for the treatment of symptomatic gallbladder disease. The present study was conducted to assess predictive factors determining conversion to open cholecystectomy in patients undergoing laparoscopic cholecystectomy.Materials & Methods: 84 patients with symptomatic gallstones and acute cholecystitis of both genders underwent laparoscopic cholecystectomies were performed by experienced laparoscopic surgeons. Rate of conversion to open cholecystectomy and reason for conversion were recorded.Results: Out of 84 patients, males were 50 and females were 34.14 were converted to open cholecystectomy. Causes were extensive intra-abdominal adhesions in 2 cases, frozen/Inflamed Calot’s triangle in 8, post ERCP status in 2, bile duct injury in 1 and cholecystoduodenal/colic fistula in 1 case. The difference was significant (P< 0.05). There were 40 male and 30 females in LC group and 10 male and 4 females in OC group. Age group (years) <60 comprised of 42 in LC and 8 in OC group and >60 years had 28 in LC and 6 in OC group. Post ERCP status was seen in 8 in LC and 2 in OC group. Previous abdominal surgery was seen in 7 in LC and 2 in OC group. Gall bladder wall thickness > 5mm was seen in 5 in LC and 7 in OC group and previous acute cholecystitis was seen in 3 in LC and 8 in OC group. The difference was significant (P< 0.05). Factors such as gender, gall bladder wall thickness > 5mm and previous acute cholecystitis was associated with open cholecystectomy.Conclusion: Presence of history of acute cholecystitis, gall bladder wall thickness >5mm and male gender were independent predictor factors for conversion from laparoscopic to open cholecystectomy.